Simvastatin in the Prevention of Recurrent Pancreatitis: Design and Rationale of a Multicenter Triple-Blind Randomized Controlled Trial, the SIMBA Trial - Cárdenas-Jaén, Karina; Vaillo-Rocamora, Alicia; Gracia, Ángel; Garg, Pramoud K.; Zapater, Pedro; Papachristou, Georgios I.; Singh, Vikesh K.; Wu, Bechien U.; de-Madaria, Enrique (Frontiers in Medicine, 2021)
Background: One every four patients with a first episode of non-gallstone-related acute pancreatitis (AP) develops recurrent disease. Recurrent episodes of acute pancreatitis or acute flares of chronic pancreatitis (CP) are associated with decreased quality of life and progression of the disease. Besides removing the etiology of pancreatitis (which sometimes is not possible), there are no effective measures to prevent recurrence . Meta-analyses of randomized controlled trials, as well as epidemiological and cohort studies suggest that statins may be protective against the development of index AP. Methods: The SIMBA study is a triple-blind randomized placebo-controlled, parallel-group multicenter trial. Patients with recurrent AP or with acute flares of CP (at least 2 episodes in the last 12 months) will be randomized to receive simvastatin 40 mg daily or placebo. During a 3-year study period, 144 patients (72 per arm of treatment) from 26 centers will be enrolled. The patients will receive the study treatment for 1 year. The primary aim is to compare the recurrence of AP or acute flares in CP. Secondary endpoints include the incidence of new-onset diabetes mellitus, new-onset exocrine pancreatic insufficiency, new-onset imaging signs of chronic pancreatitis, frequency of all-cause hospital admissions, severity of AP, adherence to treatment, and frequency of adverse events. Discussion: The SIMBA trial will ascertain whether simvastatin, a safe, widely used and inexpensive drug, can change the natural course of recurrent pancreatitis. Trial registration: ClinicalTrials.gov Identifier: NCT04021498